Indigenous Water Symbolism and Management: A Comparative Study on Ecologies of Rain and Intellectual Appropriation in Bangladesh, India, the US, and Germany - Rahman, Md Habibur; Md. Mobashir Rahman; Imroze Asif Khan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Indigenous and folk water representations are examined using the conceptual lenses